One PMP22/MPZ and Three MFN2/GDAP1 Concomitant Variants Occurred in a Cohort of 189 Chinese Charcot-Marie-Tooth Families - Xie, Yongzhi; Lin, Zhiqiang; Li, Xiaobo; Liu, Lei; Huang, Shunxiang; Zhao, Huadong; Wang, Binghao; Cao, Wanqian; Hu, Zhengmao; Guo, Jifeng; Shen, Lu; Tang, Beisha; et al. (Frontiers in Neurology, 2022)
Background and Aims: Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous group of inherited peripheral neuropathies. The wide phenotypic variability may not be completely explained by a single mutation. Aims and Methods: To explore the existence of concomitant variants in CMT, we enrolled 189 patients and performed molecular diagnosis by application of next-generation sequencing combined with multiplex ligation-dependent probe amplification. We conducted a retrospective analysis of patients harboring coinherited variants in different genes. Results: Four families were confirmed to possess variants in two genes, accounting for 2.1% (4/189) of total in our cohort. One CMT1 patient with PMP22 duplication and MPZ variant (c.286A>C, p.K96Q) exhibited moderate neuropathy with infantile onset, while her father possessing MPZ variant was mildly affected with adolescence onset. A CMT2 patient with heterozygous variants in MFN2 (c.613_622delGTCACCACAG, p.V205Sfs*26) and GDAP1 (c.713G>T, p.W238L) exhibited childhood onset mild phenotype, while his mother with MFN2 variant developed bilateral pes cavus only. A CMT2 patient with heterozygous variants in MFN2 (c.839G>A, p.R280H) and GDAP1 (c.3G>T, p.M1?) presented infantile onset and rapid progression, while her father with MFN2 variant presented with absence of deep tendon reflexes. One sporadic CMT2 patient with early onset was confirmed harboring de novo MFN2 variant (c.1835C>T, p.S612F) and heterozygous GDAP1 variant (c.767A>G, p.H256R). Conclusion: Our results suggest that the possibility of concomitant variants was not uncommon and should be considered when significant intrafamilial clinical heterogeneity is observed.